Individual differences and the perception of complex scents - Retiveau, Annlyse (Kansas State University, 2004)
Three independent panels evaluated a total of 22 scents. Two panels were highly trained in sensory analysis techniques and performed descriptive analysis of the fragrances. In the third panel, 318 untrained respondents completed demographic questionnaires, personality tests, and surveys on fragrance attitudes and behaviors. They also evaluated the 22 scents: their perceptions of the fragrances’ sensory qualities and hedonic value were recorded, as well as the images and personalities they associated with these particular fragrances. Some methodological issues were tested, emphasizing the need for standardized procedures and consistency in fragrance evaluation. The use of consistent methodology in the preparation of fragrance samples is critical to accurately assess fragrance sensory properties. Additionally, consistent use of validated questionnaires constitutes an important strength for the fragrance industry: to better understand consumers, develop marketing strategies, and improve customers’ guidance and education. The interplay of individual differences with fragrance perception, whether from an attitudinal, sensorial, hedonic, or associative standpoint, appears complex. From a perceptual standpoint, sensory profiles generated by trained panels were representative of consumers’ perceptions, yet trained panelists discriminated better among fragrances and provided more detailed and actionable profiles. From an attitudinal and behavioral standpoint, demographic and psychological differences explained independent aspects of motivations and attitudes toward fragrances, but were not sufficient to fully account for the variability in attitudinal and behavioral patterns. Lastly, in terms of fragrance perception and image and personality associations, the combination of both intrinsic sensory characteristics and fragrance hedonic value was necessary to understand patterns of image and personality traits associated with fragrances. Interestingly, most findings were consistent even when individual differences in liking patterns for fragrances were taken into account. However, some specific dimensions, such as mood associations were preferred by clusters of respondents and depended upon individual differences. Although more research is needed to better understand the interrelationships among individual differences and all aspects of fragrance perception in real-life settings, this research provided valuable insights into these phenomena – insights that have direct implications, including understanding consumer perceptual processes, assessing potential influences of fragrances on social interactions, and providing strategic planning for marketing and advertising of personal fragrances.
Keywords: Individual differences; Fragrance perception; Sensory analysis; Impression formation; Consumer acceptance; Olfaction; Agriculture, Food Science and Technology (0359); Psychology, Social (0451); Business Administration, Marketing (0338)